A case of cannibalism in Achala Cooper lizard Pristidactylus achalensis, an endemic lizard to the highest mountain areas in Central Argentina (Squamata: Leiosauridae) - Torres, María del Milagro (2019)
Cannibalism, defined by the process of eating conspecific individuals, seems to occur opportunistically as a by-product of normal predatory behaviour and generally it has been linked to island populations. Pristidactylus achalensis is an endemic specie to the highest mountains areas in central Argentina in the isolated highland ecosystem named Pampa de Achala. This species is considered omnivorous, however there are no records of either saurophagy or cannibalism. Also, it is active during the warm and rainy season, overwintering during the cold months. Therefore, the diet and feeding behaviour is a key factor for resources storage. In this note we report a case of cannibalism in a mature male of P. achalensis against a juvenile or a female recorded in the wild and discuss insights of this behaviour. Cannibalism and saurophagy are common behaviours in reptiles. For other species of the Pristidatylus genus it has been registered saurophagy cases, but has not been registered cannibalism. In this note we evidence not only saurophagy, but also cannibalism in P. achalensis, even though with this find we were not able to determine whether the prey has been dead previously or the male predated the conspecific individual. Pampa de Achala region is a mountain ecosystem with rough climate conditions and our observation was recorded at end of the lizards? active season. These characteristics could cause the lizards to appeal to cannibalism in situations of the beginning of hibernation. Also, this behaviour could be related with aggressive territoriality of males influenced by competitive dynamics. This unique observation opens new questions about the role of cannibalism in intraspecific interactions in these lizards.